Pemanfaatan Kahoot Sebagai Media Pembelajaran Interaktif Kepada Guru Sekolah Dasar - Setiawan Ardi Wijaya; Winarso, Doni; Arribe, Edo; Hafsari, Rizka; Syahril; Aryanto; Diansyah, Risnal; Mulyana, Wide; BR Bangun, Elsi Titasari (Forum Kerjasama Pendidikan Tinggi, 2025)
In the rapidly evolving digital era, education in Indonesia faces new challenges and opportunities to enhance the quality of learning. Therefore, it is crucial for teachers to upgrade their knowledge of digital-based learning methods. One solution offered is the use of interactive learning methods. In this community service project, the interactive learning medium to be explored is Kahoot. This activity collaborates with SDN 011 Lenggadai Hilir and is scheduled to take place on Wednesday, August 14, 2024. The workshop aims to improve the understanding and skills of the teachers at SDN 011 Lenggadai Hilir in utilizing Kahoot as an interactive learning medium. Kahoot is a quiz-based platform capable of creating a fun and engaging learning atmosphere for students. The research method employed in this activity is Participatory Action Research (PAR), chosen because it involves active collaboration between researchers and participants to address real-world problems and create relevant solutions. This method consists of several stages: preparation, pre-test, training, post-test, and evaluation. A pre-test is conducted to measure participants' initial knowledge of using Kahoot, followed by training that includes material presentations and hands-on practice with Kahoot. A post-test is then conducted to assess the improvement in knowledge after the training. The results of the workshop showed a significant improvement in participants' understanding. The average post-test scores were higher than the pre-test scores, indicating an increase in participants' skills in using Kahoot. The workshop also received positive feedback from participants, who felt that Kahoot could enhance student engagement in learning. This training successfully enhanced the teachers' ability to use Kahoot and motivated them to actively incorporate technology into their teaching activities.